Clinical and histopathological characteristics of breast cancer and their epidemiological trends in Trichy, Tamil Nadu: a retrospective study - S., Rathee Shree; T. , Karunaharan (International Surgery Journal, 2023)
Background: Breast cancer despite being the 2nd most commonly diagnosed, with around 68,50,00 deaths globally in 2020, has only handful of resources on the baseline characteristics, along with clinical features and histopathological findings in India. Methods: A retrospective study was done among 52 patients who presented with breast cancer proven histologically, having identified nodal status by histopathology. All the data were collected from the medical record department. Results: The mean age was found to be 42.74±11.8 years ranging from 23 to 72 years. Majority of the patients were more than 51 years old. Invasive ductal carcinoma 73.08% was the most common type observed and majority of the patients presented with stage IIb 30.77% and IIIa 28.85%. The mean size of the tumour was found to be 4.12±2.09 cm and the mean number of nodes involves were 4.60. Luminal A 42.31% was the most common immunophenotype observed followed by 23.08% of luminal B and 23.08% triple negative and rest Her2neu positive. 90.38% of the patients underwent modified radical mastectomy. Breast conservative surgery was done only among patients with stage I and II. Invasive ductal carcinoma (IDC) and invasive lobular carcinoma (ILC) was most commonly observed in right side of the breast compared to left, with upper outer quadrant being the most common site. Conclusions: Thus, comparing the results of corelation with baseline characters helps in better understanding of the traits and presentation of breast cancer in women from rural environment in Tamil Nadu.